## Solving the Equation (x+3)^2 = 36

This equation involves a squared term, which means we need to consider both positive and negative solutions. Let's break down the steps to solve it:

### 1. Taking the Square Root

First, we need to isolate the squared term by taking the square root of both sides of the equation:

√((x+3)^2) = ±√36

This gives us:

x + 3 = ±6

### 2. Isolating x

Next, we need to isolate 'x' by subtracting 3 from both sides:

x = -3 ±6

### 3. Finding the Solutions

Now, we have two possible solutions:

**x = -3 + 6 = 3****x = -3 - 6 = -9**

Therefore, the solutions to the equation (x+3)^2 = 36 are **x = 3** and **x = -9**.

### Verification

We can verify our solutions by plugging them back into the original equation:

- For x = 3: (3 + 3)^2 = 6^2 = 36
- For x = -9: (-9 + 3)^2 = (-6)^2 = 36

Both solutions satisfy the original equation.